Physico-chemical and functional properties of chicken skin collagen hydrolysate: comparative effects of Collagenase andProtease - L , Judy; Banerjee, Rituparna; Naveena, B M; Biswas, Subhashish; Gopal Patra,; D, Sowmya; Belore, Balaji; K B, Priya; P, Sowmya; P, Varakumar (Journal of Meat Science, 2025)
The present study aimed to utilize chicken skin as a source of collagen hydrolysate (CH) andto evaluate the impact of collagenase and protease enzymes on its physico-chemical andfunctional properties. Collagen hydrolysate was prepared using both conventional methods(acid and alkali treatments, water bath hydrolysis) and enzymatic treatments with collagenase(CE) and protease (PE) at aconcentration of 1:1000 w/v. A process intervention for enzymatic extraction was attempted by reducing the processing time. Compared to the conventional methods of extraction, enzymatic extraction significantly increased the yield of hydrolysates. The degree of hydrolysis (DH) indicated that enzymatic extraction enhanced the hydrolysis of collagen, with protease (PE) showing the highest DH at 72.9%, followed by collagenase (45.8%), and conventional extraction (31.8%). Enzymatic extraction resulted in superior functional properties with enhanced solubility, emulsifying properties, foaming properties, and water and oil holding capacities, which are essential for various food and industrial applications. These improved functional characteristics suggested that enzymatic pretreatment, particularly with protease, can be an effective method for producing high-quality collagen hydrolysates from chicken skin.
Keywords: Collagen hydrolysate; Enzymatic extraction; Degree of hydrolysis